9-3x=6-5x

Simple and best practice solution for 9-3x=6-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3x=6-5x equation:


Simplifying
9 + -3x = 6 + -5x

Solving
9 + -3x = 6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
9 + -3x + 5x = 6 + -5x + 5x

Combine like terms: -3x + 5x = 2x
9 + 2x = 6 + -5x + 5x

Combine like terms: -5x + 5x = 0
9 + 2x = 6 + 0
9 + 2x = 6

Add '-9' to each side of the equation.
9 + -9 + 2x = 6 + -9

Combine like terms: 9 + -9 = 0
0 + 2x = 6 + -9
2x = 6 + -9

Combine like terms: 6 + -9 = -3
2x = -3

Divide each side by '2'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| y=-2x^2+12x-18 | | 3b-10=7b+2 | | 9x^2-113x+306=0 | | x=2(3x-8) | | 2x^2(4x)=0 | | ln(x)=43 | | 8n-2=6n-15 | | 9rs-3=t | | 8x+12y=156 | | .7+1x=-.6 | | 36+7= | | 5n+2-7= | | 8(4x-2.5)=16 | | 4+-0.5y=x | | 3(1-x)=-(7x+5) | | 4(z+2)-7z=6(-0.5z+1)+2 | | 5(5c-1)-1=20c+4 | | 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 |

Equations solver categories